Pengaruh Agresivitas Pajak, Risk Minimization, dan Kepemilikan Saham Publik terhadap Pengungkapan Corporate Social Responsibility (Studi Empiris pada Perusahaan Sub Sektor Minyak, Gas, dan Batu Bara yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2020-2023 - Maya Anisa Risda; Rini Frima; Syafira Ramadhea Jr (Ekonomis: Journal of Economics and Business, 2026)
This study aims to determine the effect of tax aggressiveness, risk minimization, and public share ownership on CSR (Corporate Social Responsibility) disclosure in oil, gas, and coal sub-sector companies listed on the Indonesia Stock Exchange for the 2020-2023 period. This quantitative study uses secondary data from annual reports and sustainability reports, using a purposive sampling technique to obtain 92 observations from 23 companies. Data analysis was performed using multiple linear regression. The results of this study reveal that simultaneously there is a significant influence between the variables of tax aggressiveness, risk minimization, and public share ownership on CSR disclosure in oil, gas, and coal sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2023 period. However, partially only the risk minimization variable is proven to have a positive and significant influence on CSR disclosure.